2016
DOI: 10.1080/14740338.2016.1226279
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of infliximab in psoriatic patients over the age of 65

Abstract: Our data suggest that long-term treatment with infliximab is effective and safe in patients over 65 years old and that IV therapy is also associated with a high compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…16 A retrospective case series on the use of infliximab on 27 patients revealed a rapid and stable response over time, even though a notable discontinuation rate, mostly due to lack of efficacy and occurrence of AEs, was recorded. 17 With regard to IL-12/23 inhibitors, ustekinumab showed a clearance rate in elderly patients that was similar or slightly lower than that of younger patients, as well as low discontinuation and AE rates. 9,18,19 With respect to more recently approved drugs such as IL-17A inhibitors, we have previously reported that ixekizumab appears to be extremely effective and safe in elderly patients with psoriasis through a 1-year real-life observational study; 100% reduction in PASI (PASI100) response was reached in 81.2% of patients at week 48 without serious AEs or AEs requiring drug discontinuation.…”
Section: Discussionmentioning
confidence: 95%
“…16 A retrospective case series on the use of infliximab on 27 patients revealed a rapid and stable response over time, even though a notable discontinuation rate, mostly due to lack of efficacy and occurrence of AEs, was recorded. 17 With regard to IL-12/23 inhibitors, ustekinumab showed a clearance rate in elderly patients that was similar or slightly lower than that of younger patients, as well as low discontinuation and AE rates. 9,18,19 With respect to more recently approved drugs such as IL-17A inhibitors, we have previously reported that ixekizumab appears to be extremely effective and safe in elderly patients with psoriasis through a 1-year real-life observational study; 100% reduction in PASI (PASI100) response was reached in 81.2% of patients at week 48 without serious AEs or AEs requiring drug discontinuation.…”
Section: Discussionmentioning
confidence: 95%
“…and safety of ustekinumab in elderly patients with psoriasis, 10,11 and Chiricozzi et al 12 reported a rapid PASI score reduction and maintenance in the long term in 27 elderly patients under treatment with infliximab. The German Psoriasis Registry PsoBest reported no differences in biologics prescription in patients aged 65 or over and patients aged 35-64.…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study evaluated the long‐term efficacy and safety profile of etanercept and adalimumab, in the treatment of elderly patients affected by plaque‐type psoriasis and psoriatic arthritis . Similarly, Japanese and Italian authors reported the efficacy and safety of ustekinumab in elderly patients with psoriasis, and Chiricozzi et al . reported a rapid PASI score reduction and maintenance in the long term in 27 elderly patients under treatment with infliximab.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies PASI 75 responses range from 40 to >90%. All biologics efficacy rates is superior compared to other therapies (Chiricozzi et al, ; Vilarrasa et al, ). Biologics are now a major progress in treatment of moderate to severe psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies there are mixed levels of evidence for the long‐term efficacy of biologics. They conclude that treatment adherence and safety profile is good (Chiricozzi et al, ).…”
Section: Discussionmentioning
confidence: 99%